1988
DOI: 10.1111/j.1651-2227.1988.tb10764.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with Tonsillar Obstruction: Indications for and Efficacy of Tonsillectomy

Abstract: One hundred and twenty-two children between 1 1/2 and 14 years of age with symptoms suggesting tonsillar obstruction have been investigated. Each patient's history was analysed and the symptoms scored according to their incidence and severity. In addition, the size of the tonsils was evaluated. Eighty-five patients were chosen for tonsillectomy. The children with signs and symptoms of tonsillar obstruction improved greatly immediately after tonsillectomy. Severe symptoms of obstruction were observed in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
4
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 10 publications
3
23
4
9
Order By: Relevance
“…Problems with articulation of dento-alveolar consonants and voice resonance have been previously reported (Ahlqvist-Rastad, Hultcrantz, and Svanholm, 1988;Maryn, Van Lierde, De Bodt, and Van Cauwenberge, 2004;Mora, Crippa, Dellepiane, and Jankowska, 2007;Salami, Jankowska, Dellepiane, Crippa, and Mora, 2008).The prevalence of speech and voice disorders in children with hypertrophic tonsils is still somewhat unclear but in a study by Salami and colleagues (2008) the reported deviant /s/-production was 42,5% preoperatively.…”
Section: Introductionmentioning
confidence: 96%
“…Problems with articulation of dento-alveolar consonants and voice resonance have been previously reported (Ahlqvist-Rastad, Hultcrantz, and Svanholm, 1988;Maryn, Van Lierde, De Bodt, and Van Cauwenberge, 2004;Mora, Crippa, Dellepiane, and Jankowska, 2007;Salami, Jankowska, Dellepiane, Crippa, and Mora, 2008).The prevalence of speech and voice disorders in children with hypertrophic tonsils is still somewhat unclear but in a study by Salami and colleagues (2008) the reported deviant /s/-production was 42,5% preoperatively.…”
Section: Introductionmentioning
confidence: 96%
“…Há uma prevalência de retardo de crescimento de 1 a 46% em crianças com hipertrofia adenoamigdaliana 13,14 . Em nosso grupo, a maioria das crianças no pré-operatório encontrava-se na faixa de percentil menor que 75%, para altura e menor que 50% para peso, enquanto na população normal há um certo equilíbrio na distribuição dos indivíduos nestas faixas, em função de outros fatores, principalmente genéticos 12 .…”
Section: Discussionunclassified
“…As relativas são: tonsilites recorrentes, tonsilites associadas com doenças sistêmicas (portador do Streptococcus Betahemolítico do grupo A), abscesso peritonsilar, halitose por tonsilite caseosa. [3][4][5][6] O aparelho bisturi ultracison ou bisturi harmônico está indicado para realizar incisões em tecidos moles, quando se pretende controlar hemorragias e minimizar as lesões térmi-cas, complementando ou substituindo o eletrocautério, laser ou até mesmo o bisturi de lâmina fria.…”
Section: Introductionunclassified